Superior Accreditation Management Strategy Plan with International Reputation - Tharaba, M. Fahim; Asrori, Mohammad; Mubaroq, Zulfi; Wahyudin, Aji; Tazkiyah, I’anatut (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
Accreditation is a crucial indicator of quality assurance in educational institutions, ensuring compliance with national and international academic standards. It serves as formal recognition of an institution’s commitment to excellence, providing credibility and fostering continuous improvement. UIN Maulana Malik Ibrahim Malang has consistently pursued the highest accreditation standards, as evidenced by several study programs achieving superior ratings and the institution’s continuous efforts toward international certification. However, achieving and maintaining superior accreditation requires a well-structured and strategic approach. This study aims to develop and analyze a strategic planning model to optimize the accreditation process and strengthen the institution’s global reputation. Employing a qualitative research method with a bibliographic review approach, the study adopts the strategic management model by David F.R., which comprises five key stages: initial assessment, situational analysis, strategy formulation, implementation, and monitoring. This comprehensive model ensures a systematic and structured approach to accreditation, enabling institutions to align their strategies with accreditation requirements effectively. The findings indicate that this integrated model significantly enhances accreditation management by providing a clear roadmap for institutions to follow. Moreover, it introduces an innovative framework by combining established strategic planning principles with customized measurement tools, ensuring that accreditation processes are both efficient and sustainable. As a result, this approach not only facilitates the achievement of superior accreditation but also strengthens UIN Malang’s position as a leading Islamic higher education institution with a vision of international excellence. This study offers valuable insights for higher education institutions striving for quality assurance, accreditation optimization, and global recognition.